DEVELOPMENT OF TEACHING MATERIALS OF TEMBUNG (UPDATE CONTINUOUS) IN CLASS I ELEMENTARY SCHOOL - Urip Umayah (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2022)
Curriculum writing is one of the language skills that must be mastered by lower grade elementary school students in accordance with the competency standards demanded by the curriculum. In fact, there are still many students who have not mastered the skill of writing tembung (upright cursive) because some students write with tembung which is very complicated, so that only a few skilled students are able to achieve the KKM. The development of tebung teaching materials is an alternative to improve the writing skills of elementary school students. The purpose of this study is "Describe the analysis of student writing tebung in the development of teaching materials in elementary school". This study uses the Design and Development (D&D) method which was carried out at SDN 01 Gayamsari Semarang and SDN 02 Rejosari Semarang, the research subjects were 88 first grade elementary school students, 2 content or material expert lecturers, 1 design expert lecturer and 2 lower grade elementary school teachers. Data collection techniques in the form of interviews with homeroom I, distribution of teaching material validation questionnaires developed by researchers to expert lecturers and elementary school teachers. The data collected through the distribution of questionnaires were then analyzed using a Likert Scale. The results of the research on writing student tembung are still below the KKM. The teaching materials developed resulted in a product in the form of a writing guide book with the results of product trials, namely Very Good so that it was feasible to use.